Earthquake proof design and active faults - Kanaori, Yuji, 1951- (Developments in geotechnical engineeiing ;, 1997)
On 17th January 1995 an inland earthquake of 7.2 magnitude occurred under Kobe city in central Japan. More than 5,500 people lost their lives. There was immense and serious damage to buildings. Researchers and engineers were shocked and astonished by the extent of the devastation and loss of life. Ground motions, generated by the event were far greater than the seismic standard for earthquake-proof designs in Japan. Recent academic progress in the fields of geology and geophysics, which would help to reduce the severity of seismic disasters, has not been sufficiently applied to the development of earthquake-proof designs. This book contains 13 original and innovative papers of interdisciplinary study spanning earthquake-proof technology and active fault science (seven of the papers cover topics concerning the 1995 Kobe earthquake).